Splošna matura na Slovenskem - Bucik, Valentin (Sodobna pedagogika, 2009)
Matura final examination in Slovenia gymnasium is fourteen years old. In the frame of discussion about changes at the secondary level of education - gymnasium in particular - there is an opportunity to raise some important questions regarding possible changes, improvements, modernisation or even cancellation of matura. In the paper the discuission is opened about the contents and structure of matura, reasons for its initial introduction insteadof entrance-examinations at the universities, its purpose, goals and effects. The report about the current and constant efforts to make matura as a final act in the series of gymnasium examinations better is also presented. Above all some determinants of matura are listed and explained that should stay relatively constant in the line of changes and others that should urgently be modified and improved in order to reach better and more balanced matura model.
Keywords: matura; preverjanje znanja; ocenjevanje; Slovenia; Slovenija